Behavioral Counseling to Promote a Healthful Diet and Physical Activity for Cardiovascular Disease Prevention in Adults Without Known Cardiovascular Disease Risk Factors: Updated Systematic Review for the U.S. Preventive Services Task Force [Internet] - Alhejaili, Basim Eid; Alrehaili, Riyadh Saleh; Balubaid, HUSSAM Mohammed; amashah, Hadeel hassan; Alalawi, Khaled Jumah; Alharbi, Jamal Said Saadi; Alshehri, Shroug Hussain; Alsubhi, Abdulhakim Abdulrahman Mesfer; alharbi, Waleed khalid alyan; ALRUWAYTHI, AHMED ABDULAZIZ SALEH; SIBAA, MOHAMMED IBRAHIM MOHAMMEDALI BIN; Al johani, Rami Ibrahim kuraydim; et al. (Journal of Ecohumanism, 2024)
Background: A healthy diet is characterized by a balanced and varied selection of meals and drinks that aids a person in attaining and sustaining a healthy weight. Aim: To carefully assess the proof regarding the harm and benefits of behavior therapy for the 1ry avoidance of cardiovascular illness in adults lacking recognized cardiovascular risk factors to educate the United States Preventive Services Task Force. Materials and methods: This systematic review and meta-analysis encompassed nine research studies, submitting to the Cochrane Collaboration principles and conforming to the PRISMA declaration (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Main findings: Behavioral interventions enhanced levels of nutritional consumption and physical activity, with consistent benefits for healthful diets versus controls at 6+ months. Small, although significant variations have been detected in systolic blood pressure (−1.26 millimeters mercury [ninety-five percent confidence interval, −1.77 to −0.75]), total cholesterol (−2.85 milligrams per deciliter [ninety-five percent confidence interval, −4.95 to −0.75]), in addition to body mass index (−0.41 [ninety-five percent confidence interval, −0.62 to −0.19]) at the six- to twelve-month interval. Modest correlations with activity and dietary behaviors were observed, with no increased adverse events in intervention participants. Conclusion: Behavioral interventions significantly improve levels of dietary intake and physical activity, with healthy diets and programs showing significant benefits over 6+ months. Small improvements in blood pressure, cholesterol, and BMI were noted, with tailored approaches being particularly effective without increased adverse events